Analisis Manajemen Resiko Teknologi Informasi dan Pemetaan Maturity Level menggunakan Framework COBIT 4.1 (Studi Kasus: PT. CAHAYA BINTANG): Fitri Annisa Purba - Purba, Fitri Annisa (Jurnal Teknologi dan Manajemen Sistem Industri, 2024)
The rapid growth of information technology forces businesses to continuously adapt and utilize new innovations, offering solutions for operational, business, and financial challenges. However, implementing IT requires a framework to identify risks and create mitigation strategies. Despite its benefits, IT carries risks of failure and high investment costs, necessitating consistent oversight. Companies must adopt risk management practices to understand and manage these risks. The COBIT 4.1 framework helps align IT with business processes, assess and manage risks, evaluate maturity levels, and offer recommendations. This study follows a multi-stage approach, including literature review, risk identification, assessment, response planning, and maturity evaluation.